Toxocara and toxocariasis - Bowman, Dwight D. (Advances in parasitology ;, 2020)
Toxocara and Toxocariasis, Volume 109 in the Advances in Parasitology series, includes medical studies of parasites of major influence, along with reviews of more traditional areas, such as zoology, taxonomy and life history, all topics which help to shape current thinking and applications. This latest release includes chapters on organism and the recognition of the disease, dogs (and cats) disease, diagnosis, prevalence of infection, and treatment, and more.